Application of Oketani Massage to Increase Breast Milk Production in Postpartum Mothers After Caesarean Section at dr. Adhyatma, MPH Regional General Hospital, Central Java Province - Ida Novi Fitriyani; Witri Hastuti (Jurnal EduHealth, 2025)
Postpartum mothers who undergo Caesarean section often experience delayed lactation, leading to insufficient breast milk production. This case study aims to describe the application of Oketani massage as a complementary therapy to enhance breast milk production in postpartum Caesarean section mothers at RSUD Dr. Adhyatma, MPH, Central Java Province. A descriptive case study design was employed involving three clients who met the inclusion criteria. Oketani massage was provided twice daily for 15 minutes over three consecutive days. Data were collected through assessment, interviews, observation, and documentation, and were analyzed based on changes in breastfeeding frequency, expressed breast milk volume, infant urination and defecation frequency, and LATCH scores before and after the intervention. The results showed improvements in breast milk production, breastfeeding frequency, infant elimination patterns, and LATCH scores in all clients. Outcome variations were influenced by maternal age, nutritional intake, and education level. These findings indicate that Oketani massage is a beneficial non-pharmacological intervention to support lactation among postpartum Caesarean section mothers and may be integrated into maternal nursing care to promote breastfeeding success.